Alignment of Indonesian Manpower Regulations with ILO Standards in Increasing the Participation of Persons with Disabilities in the World of Work - Dewi, E. Imma Indra; Angelia, Shella (Westscience Press, 2025)
The protection of employment rights for persons with disabilities is an important part of efforts to realize equality and human dignity. This study aims to examine the legal framework in Indonesia related to employment for persons with disabilities by assessing its conformity to the standards set by the International Labour Organization (ILO). Using normative legal research methods, this study focuses on the analysis of relevant national regulations as well as international conventions that have been ratified by Indonesia, especially those related to the rights of persons with disabilities in the workplace. This study reviews whether existing legal provisions in Indonesia have adopted the principles outlined in the ILO standards, as well as provides a critical review of legal measures in Indonesia. The results of the study show that there is a conformity in several aspects between the Indonesian legal framework and ILO standards, but there are still some things that need to be improved in legislation to improve legal protection for persons with disabilities in Indonesia.